Electrolyte and application thereof
By introducing halogenated naphthalene as additives into the lithium-ion battery electrolyte, the problem of poor compatibility of the negative electrode side of the graphite in the lithium-ion battery is solved, and a stable interface mask is formed, which improves the battery cycle stability and Coulomb efficiency and extends the battery life.
Patent Information
- Application Number
- CN202411793160.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium-ion battery electrolyte has poor compatibility on the negative electrode side of the graphite, resulting in unstable lithium-ion deintercalation and affecting the battery cycle performance and life.
Halogenated naphthalene is used as an additive for electrolyte. By interacting with solvents, the interaction between lithium ions and solvents is weakened, the reversible deintercalation of lithium ions is promoted, and a stable protective interface film is formed on the negative electrode side of the graphite to prevent the solvent from being embedded together. .
It significantly improves the cycle stability and Coulomb efficiency of lithium-ion batteries, extends the battery life, prevents the graphite layer from peeling off, and improves the battery compatibility and circulation performance.
Smart Images

Figure CN119275353A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an electrolyte and application thereof, belonging to the technical field of battery electrolytes. Background Art
[0002] Ion intercalation chemistry is the basis of electrochemical energy storage in secondary batteries, which is manifested in the embedding and extraction of cations or anions in electrode materials and the transmission of electrons in the external circuit, which together realize the storage and conversion of energy. + In the positive electrode (such as LiCoO2, LiFePO4, LiNi 0.5 Mn 1.5 The reversible embedding and extraction (i.e., de-embedding) of ions in the electrolyte and the electrode interface is closely related to the state of the ions at the electrolyte and electrode interface.
[0003] The electrolyte is usually composed of lithium salts, solvents, and additives to ensure the transport of ions during the charge and discharge process. The electrolyte determines the migration rate of lithium ions between the positive and negative electrodes, and participates in the formation of SEI. Therefore, it greatly affects the internal resistance, capacity, cycle performance, rate performance, specific energy, rate charge and discharge performance, operating temperature range, life, storage, safety, self-discharge performance and overcharge behavior of the battery. The solvent is closely related to the properties of the electrolyte. With a few exceptions, the solvent usually occupies the largest part of the electrolyte, whether by weight, volume or mole fraction. Propylene carbonate (PC) has a high dielectric constant, a wide liquid range, and good static stability with lithium metal, which makes it the first choice for solvents. However, propylene carbonate-based electrolytes are incompatible with graphite and there is Li + -PC co-embeds graphite, causing the graphite layer to peel off. Ethyl acetate (EA), acetonitrile (AN), etc. have the advantages of appropriate dielectric constant, low viscosity and low melting point, but they cannot form a protective solid electrolyte interface film (SEI) and have poor negative electrode stability. The use of additives can effectively improve the above situation. The content of additives in the electrolyte is up to 5% (wt% or vol%). Although the amount is small, this amount may introduce some negative effects for the electrolyte, such as increased impedance, etc. A large amount of addition will increase the internal resistance of the battery, reduce the conductivity, reduce the capacity of the battery, and even destroy the internal structure of the battery, corrode the electrode material, and is not conducive to the stable cycle of the battery. Therefore, finding additives that can effectively modify the electrolyte with low addition is an economical choice to promote the application of solvents such as propylene carbonate, ethyl acetate, and acetonitrile in lithium-ion batteries. Summary of the invention
[0004] In view of this, the present application first provides an electrolyte, which aims to improve the cycle stability of lithium-ion batteries, form a good interface film on the negative electrode side while retaining good compatibility with the positive electrode side, and greatly improve the application scope of various solvents in lithium batteries.
[0005] Specifically, the present application is implemented through the following scheme: An electrolyte comprises a lithium salt, a solvent and an additive, wherein the additive comprises a naphthalene halide, wherein the chemical formula of the naphthalene halide is C x H y X z , X is a halogen, x, y, z are all positive integers or 0, and 2x+1=y+z.
[0006] Further, as a preference: The halogenated naphthalene structure is as follows: , At least one of R1, R2, R3, R4, R5, R6, R7, and R8 is selected from F, Cl, or Br, and the remaining substituents are H or alkyl groups. When an alkyl group is contained, a halogenated alkylnaphthalene is formed.
[0007] In the electrolyte, the mass percentage of the halogenated naphthalene is not less than 0.01%.
[0008] The halogenated naphthalene includes at least one of 1-bromo-4-fluoronaphthalene, 1,2,3,4-tetrafluoronaphthalene, 1,2,3,4,5,6-hexafluoronaphthalene, 1,2,3,6,7,8-hexafluoronaphthalene, 1,2,3,4,5,6,8-heptafluoronaphthalene, 1,2,3,4,5,6,7-heptafluoronaphthalene, 2-bromoheptafluoronaphthalene, octafluoronaphthalene, 1-(difluoromethyl)naphthalene, and 1-(trifluoromethyl)-naphthalene. More preferably, the halogenated naphthalene is at least one of 1-bromo-4-fluoronaphthalene, 2-bromoheptafluoronaphthalene, octafluoronaphthalene, and 1-(difluoromethyl)naphthalene.
[0009] The lithium salt is at least one of inorganic anion lithium salts and organic anion lithium salts such as lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate), lithium (fluorosulfonyl) (trifluoromethylsulfonyl) imide, lithium nitrate, lithium hexafluorophosphate, and lithium tetrafluoroborate. More preferably, the lithium salt is at least one selected from lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.
[0010] The lithium salt concentration in the electrolyte is 1.0-2.0 M. More preferably, the lithium salt concentration in the electrolyte is 1.0-1.5 M.
[0011] The solvent is any one of propylene carbonate, acetonitrile and ethyl acetate.
[0012] The second object of the applicant is to provide an application of the above electrolyte, that is, for a lithium-ion battery, wherein the lithium-ion battery comprises a positive electrode material, a negative electrode material and the electrolyte having the above characteristics. The introduction of the above electrolyte can prevent graphite co-embedding in the lithium-ion battery.
[0013] The positive electrode material includes a ternary positive electrode (NCM811) material and a lithium iron phosphate (LFP) material.
[0014] The negative electrode material includes graphite.
[0015] The electrolyte is used for graphite||LiFePO4 battery, Li||graphite battery or graphite||LiNi 0.8 Co 0.1 Mn 0.1 O2 battery.
[0016] Advantages and technical effects of the electrolyte for lithium-ion batteries in this application: 1. This application uses halogenated naphthalene (including halogenated alkyl naphthalene) as an additive to the electrolyte. Due to the interaction between the halogen atoms of the halogenated naphthalene and the solvent, the Li + -Solvent interactions effectively promote the Li + The desolvation process of Li + Reversible deintercalation and insertion in graphite is achieved. At the same time, Li + The interaction with the solvent is weakened, allowing the anions to participate more in the solvation sheath. The anions are reduced at the graphite anode to form an inorganic product-rich SEI film, which prevents the solvent from being co-embedded in the graphite. 2. The electrolyte of the present application can effectively improve the compatibility between the electrolyte and the graphite negative electrode; 3. The electrolyte of the present application has excellent compatibility with the positive and negative electrodes, achieving a long cycle life and high coulombic efficiency of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 (a) is the electrolyte prepared in Example 1 on graphite||LiNi 0.8 Co 0.1 Mn 0.1 Schematic diagram of cycle life test in O2 battery, Figure 1(b) is the voltage-current curve of the Li||graphite battery of the electrolyte prepared in Example 1. Figure 1 (c) is a schematic diagram of a cycle life test of a Li||graphite battery of the electrolyte prepared in Example 1; Figure 2 (a) is the voltage-current curve of the electrolyte prepared in Example 2 in a graphite||LiFePO4 battery, Figure 2 (b) is the voltage-current curve of the Li||graphite battery of the electrolyte prepared in Example 2, Figure 2 (c) is a schematic diagram of a cycle life test of a Li||graphite battery of the electrolyte prepared in Example 2; Figure 3 (a) is the electrolyte prepared in Example 3 on graphite||LiNi 0.8 Co 0.1 Mn 0.1 Schematic diagram of cycle life test in O2 battery, Figure 3 (b) is the voltage-current curve of the Li||graphite battery of the electrolyte prepared in Example 3, Figure 3 (c) is a schematic diagram of the cycle life test of the Li||graphite battery of the electrolyte prepared in Example 3; Figure 4 (a) is the electrolyte prepared in Example 4 on graphite||LiNi 0.8 Co 0.1 Mn 0.1 Schematic diagram of cycle life test in O2 battery, Figure 4 (b) is the voltage-current curve of the Li||graphite battery of the electrolyte prepared in Example 4, Figure 4 (c) is a schematic diagram of a cycle life test of a Li||graphite battery of the electrolyte prepared in Example 4; Figure 5 (a) is the electrolyte prepared in Comparative Example 1 on graphite||LiNi 0.8 Co 0.1 Mn 0.1 Schematic diagram of cycle life test in O2 battery, Figure 5 (b) is the voltage-current curve of the electrolyte prepared in Comparative Example 1 in a graphite||LiFePO4 battery. Figure 5 (c) is a schematic diagram of the cycle life test of the Li||graphite battery of the electrolyte prepared in Comparative Example 1, Figure 5 (d) is the voltage-current curve of the Li||graphite battery of the electrolyte prepared in Comparative Example 1; Figure 6 (a) is the electrolyte prepared in Comparative Example 2 on graphite||LiNi 0.8 Co 0.1Mn 0.1 Voltage-current curve in O2 battery, Figure 6 (b) is the voltage-current curve of the electrolyte prepared in Comparative Example 2 in a graphite||LiFePO4 battery. Figure 6 (c) is the voltage-current curve of the Li||graphite battery of the electrolyte prepared in Comparative Example 2; Figure 7 (a) is the electrolyte prepared in Comparative Example 3 on graphite||LiNi 0.8 Co 0.1 Mn 0.1 Voltage-current curve in O2 battery, Figure 7 (b) is the voltage-current curve of the Li||graphite battery of the electrolyte prepared in Comparative Example 3; Figure 8 (a) is the electrolyte prepared in Comparative Example 4 on graphite||LiNi 0.8 Co 0.1 Mn 0.1 Voltage-current curve in O2 battery, Figure 8 (b) is the voltage-current curve of the Li||graphite battery of the electrolyte prepared in Comparative Example 4. DETAILED DESCRIPTION
[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0020] Example 1 This embodiment provides an electrolyte, and its preparation method is as follows: Lithium bis(fluorosulfonyl)imide was slowly dissolved in propylene carbonate and stirred until the electrolyte was completely clear. The lithium salt concentration in the electrolyte was controlled to be 1.0 M (M = mol / L), and 1% of 1-bromo-4-fluoronaphthalene was added.
[0021] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 1 shown.
[0022] Figure 1 (a) is the electrolyte in graphite||LiNi 0.8 Co 0.1 Mn 0.1Cycle life curve of O2 battery, where the surface capacity of NCM811 electrode is 2.63 mAh cm -2 The test voltage range is 2.8 V~4.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the capacity retention rate after 150 cycles is 99.04%, and the average coulombic efficiency exceeds 99.95%.
[0023] Figure 1 (b) shows the voltage-current curves of the first, 50th, 100th, and 150th cycles of the Li||graphite battery with electrolyte. The three lithium insertion platforms are clearly visible in the image.
[0024] Figure 1 (c) is a schematic diagram of the cycle life test of the Li||graphite battery with electrolyte. The surface capacity of the graphite electrode is 1.53 mAh cm -2 The test voltage range is 0.001 V~1.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the capacity retention rate after 150 cycles is 96.89%, and the average coulombic efficiency exceeds 99.88%.
[0025] Example 2 This embodiment provides an electrolyte, and its preparation method is as follows: Lithium bis(fluorosulfonyl)imide was slowly dissolved in propylene carbonate and stirred until the electrolyte was completely clear. The prepared electrolyte had a lithium salt concentration of 1.0 M (M = mol / L) and 1% by mass of 2-bromoheptafluoronaphthalene was added.
[0026] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 2 shown.
[0027] Figure 2 (a) shows the voltage-current curve of the electrolyte in the graphite||LiFePO4 battery, where the surface capacity of the LFP electrode is 3.23 mAh cm -2 The test voltage range is 2.8 V~3.8 V, and the test rate is 0.1 C for 3 cycles of charge and discharge. It can be seen that the battery assembled with this electrolyte has higher efficiency and can release higher capacity. Compared with traditional commercial ester-based electrolytes, the performance has been greatly improved.
[0028] Figure 2 (b) shows the voltage-current curves of the first, 50th, 100th, and 150th cycles of the Li||graphite battery with electrolyte. The three lithium insertion platforms are clearly visible in the image.
[0029] Figure 2(c) is a schematic diagram of the cycle life test of the Li||graphite battery with electrolyte. The surface capacity of the graphite electrode is 1.25 mAh cm -2 The test voltage range is 0.001 V~1.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the capacity retention rate is 96.72% after 150 cycles, and the average coulombic efficiency exceeds 99.97%. Compared with traditional commercial ester-based electrolytes, the cyclability has been greatly improved.
[0030] Example 3 This embodiment provides an electrolyte, and its preparation method is as follows: Lithium bis(fluorosulfonyl)imide was slowly dissolved in acetonitrile and stirred until the electrolyte was completely clear. The prepared electrolyte had a lithium salt concentration of 1.0 M (M = mol / L) and 5% by mass of octafluoronaphthalene was added.
[0031] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 3 shown.
[0032] Figure 3 (a) is the electrolyte in graphite||LiNi 0.8 Co 0.1 Mn 0.1 Cycle life test curve of O2 battery, where the surface capacity of NCM811 electrode is 3.57 mAh cm -2 The test voltage range is 2.8 V~4.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the capacity retention rate is 90.54% after 150 cycles, and the average coulombic efficiency exceeds 99.85%. Compared with traditional commercial ester-based electrolytes, the cyclability has been greatly improved.
[0033] Figure 3 (b) shows the voltage-current curves of the first, 50th, 100th, and 150th cycles of the Li||graphite battery with electrolyte. The three lithium insertion platforms are clearly visible in the image.
[0034] Figure 3 (c) is a schematic diagram of the cycle life test of the Li||graphite battery with electrolyte. The surface capacity of the graphite electrode is 2.34 mAh cm -2 The test voltage range is 0.001 V~1.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the capacity retention rate is 98.49% after 150 cycles, and the average coulombic efficiency exceeds 99.75%. Compared with traditional commercial ester-based electrolytes, the cyclability has been greatly improved.
[0035] Example 4 This embodiment provides an electrolyte, and its preparation method is as follows: Lithium bis(fluorosulfonyl)imide was slowly dissolved in ethyl acetate and stirred until the electrolyte was completely clear. The prepared electrolyte had a lithium salt concentration of 1.0 M (M = mol / L) and 5% by mass of 1-(difluoromethyl)naphthalene was added.
[0036] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 4 shown.
[0037] Figure 4 (a) is the electrolyte in graphite||LiNi 0.8 Co 0.1 Mn 0.1 Cycle life curve of O2 battery, where the surface capacity of NCM811 electrode is 1.63 mAh cm -2 The test voltage range is 2.8 V~4.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the capacity retention rate is 99.59% after 150 cycles, and the average coulombic efficiency exceeds 99.95%. Compared with traditional commercial ester-based electrolytes, the cyclability has been greatly improved.
[0038] Figure 4 (b) shows the voltage-current curves of the first, 50th, 100th, and 150th cycles of the Li||graphite battery with electrolyte. The three lithium insertion platforms are clearly visible in the image.
[0039] Figure 4 (c) is a schematic diagram of the cycle life test of the Li||graphite battery with electrolyte. The surface capacity of the graphite electrode is 1.17 mAh cm -2 The test voltage range is 0.001 V~1.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the capacity retention rate is 98.41% after 150 cycles, and the average coulombic efficiency exceeds 99.90%. Compared with traditional commercial ester-based electrolytes, the cyclability has been greatly improved.
[0040] Comparative Example 1 This comparative example is a conventional commercial ester-based electrolyte for lithium batteries, and the electrolyte preparation method is as follows: A certain amount of lithium hexafluorophosphate is slowly dissolved in ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, so that the concentration of lithium hexafluorophosphate is 1.0 mol / L. Stir until the electrolyte is completely clear to obtain a commercial ester-based electrolyte for lithium batteries.
[0041] The commercial ester-based electrolyte with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 5shown.
[0042] Figure 5 (a) is the electrolyte in graphite||LiNi 0.8 Co 0.1 Mn 0.1 Cycle life curve of O2 battery, where the surface capacity of NCM811 electrode is 0.88 mAh cm -2 The test voltage range is 2.8 V~4.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the capacity retention rate after 150 cycles is only 82.13%, and the average coulombic efficiency is much less than 99.6%.
[0043] Figure 5 (b) shows the voltage-current curve of the electrolyte in the graphite||LiFePO4 battery, where the surface capacity of the LFP electrode is 4.23 mAh cm -2 The test voltage range is 2.8 V~3.8 V, and the test rate is 0.1 C charge and discharge for 3 cycles. It can be seen that the comparison sample can barely support the operation of the battery, and its efficiency and capacity retention rate are low.
[0044] Figure 5 (c) is a schematic diagram of the cycle life test of the Li||graphite battery with electrolyte. The surface capacity of the graphite electrode is 0.62 mAh cm -2 The test voltage range is 0.001 V~1.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the capacity retention rate after 150 cycles is 91.77%, and the average coulombic efficiency is 98.9%.
[0045] Figure 5 (d) shows the voltage-current curves of the first, 50th, 100th, and 150th cycles of the Li||graphite battery with electrolyte, showing three clear lithium insertion platforms.
[0046] Comparison of Graphite||LiNi in Examples 1 to 4 and Comparative Example 1 0.8 Co 0.1 Mn 0.1 It can be seen from the O2 battery cycle life curve and the Li||graphite battery cycle life curve that the cyclability and cycle stability of this case have been greatly improved.
[0047] Comparative Example 2 The electrolyte preparation method of this comparative example is as follows: A certain amount of lithium bis(fluorosulfonyl)imide was slowly dissolved in propylene carbonate to make the concentration of lithium bis(fluorosulfonyl)imide 1.0 mol / L. The electrolyte was stirred until it was completely clear to obtain a comparative electrolyte.
[0048] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 6 shown.
[0049] Figure 6 (a) is the electrolyte in graphite||LiNi 0.8 Co 0.1 Mn 0.1 Voltage-current curves in an O2 battery, where the surface capacity of the NCM811 electrode is 1.64 mAh cm -2 The test voltage range is 2.8 V~4.5 V, the test rate is 0.1 C charge and discharge for 2 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the comparison sample cannot achieve normal cycling.
[0050] Figure 6 (b) shows the voltage-current curve of the electrolyte in the graphite||LiFePO4 battery, where the surface capacity of the LFP electrode is 4.58 mAh cm -2 The test voltage range is 2.8 V~3.8 V, and the test rate is 0.1 C for 3 cycles. However, in the second cycle, the comparison sample cannot support normal cycling.
[0051] Figure 6 (c) shows the voltage-current curve of the Li||graphite battery with electrolyte, where the surface capacity of the graphite electrode is 1.24 mAh cm -2 The test voltage range is 0.001 V~1.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. The image shows an obvious solvent co-embedded platform, that is, the comparative sample is not compatible with the graphite electrode and is not suitable as a lithium-ion battery electrolyte.
[0052] Comparative Example 3 The electrolyte preparation method of this comparative example is as follows: A certain amount of lithium bis(fluorosulfonyl)imide was slowly dissolved in acetonitrile to make the concentration of lithium bis(fluorosulfonyl)imide 1.0 mol / L. The electrolyte was stirred until it was completely clear to obtain a comparative electrolyte.
[0053] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 7 shown.
[0054] Figure 7 (a) is the electrolyte in graphite||LiNi 0.8 Co 0.1 Mn 0.1 Voltage-current curves in an O2 battery, where the surface capacity of the NCM811 electrode is 1.14 mAh cm -2The test voltage range is 2.8 V~4.5 V, the test rate is 0.1 C charge and discharge for 2 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the comparison sample cannot achieve normal cycling.
[0055] Figure 7 (b) shows the voltage-current curve of the Li||graphite battery with electrolyte, where the surface capacity of the graphite electrode is 1.89 mAh cm -2 The test voltage range is 0.001 V~1.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for a long cycle. As can be seen from the image, the comparative sample is not compatible with the graphite electrode and is not suitable as a lithium-ion battery electrolyte.
[0056] Comparative Example 4 The electrolyte preparation method of this comparative example is as follows: A certain amount of lithium bis(fluorosulfonyl)imide was slowly dissolved in ethyl acetate to make the concentration of lithium bis(fluorosulfonyl)imide 1.0 mol / L. The electrolyte was stirred until it was completely clear to obtain a comparative electrolyte.
[0057] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 8 shown.
[0058] Figure 8 (a) is the electrolyte in graphite||LiNi 0.8 Co 0.1 Mn 0.1 Voltage-current curves in an O2 battery, where the surface capacity of the NCM811 electrode is 2.36 mAh cm -2 The test voltage range is 2.8 V~4.5 V, the test rate is 0.1 C charge and discharge for 2 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the comparison sample cannot achieve normal cycling.
[0059] Figure 8 (b) shows the voltage-current curve of the Li||graphite battery with electrolyte, where the surface capacity of the graphite electrode is 0.96 mAh cm -2 The test voltage range is 0.001 V~1.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for a long cycle. It can be seen from the image that the comparative sample is not compatible with the graphite electrode and is not suitable as a lithium-ion battery electrolyte.
[0060] By comparing the above embodiments and comparative examples, it can be seen that the electrolyte provided by the present application has good performance in preventing the solvent from being co-embedded in graphite. The introduction of additives can form a stable interface protection layer on the negative electrode side, prevent the solvent from being co-embedded in the graphite layer, and reduce the side reactions of the electrolyte, thereby achieving excellent cycle performance. When applied, it can match the lithium iron phosphate positive electrode and the high-voltage positive electrode material, and the formed graphite||LFP battery can be circulated normally. The capacity retention rate of the graphite||NMC811 battery is still above 99.6% after more than 150 cycles, and the coulombic efficiency exceeds 99.9%. At the same time, the Li||graphite battery assembled using the electrolyte provided by the present application has three clearly visible lithium-embedded platforms, and its stable cycle is more than 150 cycles and still has a capacity retention rate of more than 98.4%, realizing the application and stable cycle of a type of solvent co-embedded with graphite such as propylene carbonate in lithium-ion batteries.
[0061] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.
Claims
1. An electrolyte, characterized in that: The invention comprises a lithium salt, a solvent and an additive, wherein the additive comprises a halogenated naphthalene, and the chemical formula of the halogenated naphthalene is C x H y X z , X is a halogen, x, y, z are all positive integers or 0, and 2x+1=y+z, and the mass percentage of halogenated naphthalene in the electrolyte is not less than 0.01%.
2. An electrolyte according to claim 1, characterized in that: At least one of the eight substituents of the halonaphthalene is selected from F, Cl or Br.
3. An electrolyte according to claim 1, characterized in that: The halogenated naphthalene is any one of 1-bromo-4-fluoronaphthalene, 1,2,3,4-tetrafluoronaphthalene, 1,2,3,4,5,6-hexafluoronaphthalene, 1,2,3,6,7,8-hexafluoronaphthalene, 1,2,3,4,5,6,8-heptafluoronaphthalene, 1,2,3,4,5,6,7-heptafluoronaphthalene, 2-bromoheptafluoronaphthalene, octafluoronaphthalene, 1-(difluoromethyl)naphthalene and 1-(trifluoromethyl)-naphthalene.
4. An electrolyte according to claim 1, characterized in that: The mass percentage of the halogenated naphthalene in the electrolyte is 1-5%.
5. An electrolyte according to claim 1, characterized in that: The lithium salt is lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate), lithium (fluorosulfonyl)(trifluoromethylsulfonyl)imide, lithium nitrate, lithium hexafluorophosphate, lithium tetrafluoroborate or an organic anion lithium salt.
6. An electrolyte according to claim 1, characterized in that: The lithium salt concentration is 1.0~2.0 M.
7. An electrolyte according to claim 1, characterized in that: The solvent is any one of propylene carbonate, acetonitrile and ethyl acetate.
8. An application of an electrolyte, characterized in that: The electrolyte is used in a lithium-ion battery. The lithium-ion battery comprises a positive electrode material, a negative electrode material and the electrolyte according to claim 1.
9. The use of an electrolyte according to claim 8, characterized in that: The positive electrode material is a ternary positive electrode material or a lithium iron phosphate material, and the negative electrode material is graphite.
10. The use of an electrolyte according to claim 8, characterized in that: The electrolyte is used for graphite||LiFePO4 battery, Li||graphite battery or graphite||LiNi 0.8 Co 0.1 Mn 0.1 O2 battery.
Citation Information
Patent Citations
Wettability-enhanced lithium ion battery electrolyte and application thereof
CN114421008A
Organic electrolyte secondary battery
JP1998112335A
Organic electrolytic solution secondary battery
JP2003132950A